Termoinibição em sementes de alface em função da posição da flor e do armazenamento - Fonseca, Roberta (2016)
Lettuce is one of the vegetables with the highest expression in the world. Its consumption is growing every year in Brazil and expanded the production areas for different regions. However, a limitation for its production is the occurrence of high temperatures during the germination, which takes most cultivars do not germinate at temperatures above 28 ° C. However, the Everglades cultivar shows germination of 60 to 70%, on average 35ºC, considered tolerant germination at high temperature (tolerant thermo inhibition).. On the other hand, also a factor that normally prevents / reduces germination soon after harvesting is the primary dormancy. The position of the seed in the mother plant is an aspect that can influence the dormancy of lettuce seeds. Thus, the aim of this work was to evaluate the influence of the position of the seed in the mother plant and the effect of Everglades cultivar lettuce seed germination in storage at 35 ° C temperature, and analyze the levels of enzymes and proteins heat tolerant. The experiments were conducted in the experimental area of HortiAgro Sementes S/A and Seed Analysis Laboratory (UFLA). Were obtained progenies of Everglades cultivars (tolerant thermoinhibition) and Veronica (sensitive to thermoinhibition) from germinated seeds in temperatures of 20 and 35 ° C, the seeds, object of study, collected in two parts of the inflorescence (apex and base). The seeds of the progenies were evaluated by germination in four seasons after harvest (70, 130, 190 and 400 days), these were also evaluated activity of endo-β-mannanase enzyme and standard resistant protein to heat to 400 days after the harvest. There was no difference in seed germination as to its origin in the previous generation, both in plants grown from seeds that germinated at 20 or 35 ° C. Was also not found difference in the position of the seed in the mother plant inflorescences. On the other hand, there were differences between the progenies of "Everglades" and the storage times. The Everglades cultivar showed to be tolerant thermoinhibition compared to cultivate Veronica and that this tolerance is affected by the primary dormancy / thermoinhibition. Overall there was no direct relationship between the progenies, the percentage of germination and enzyme activity. It was also found that the expression of the protein and the activity of endo-β-mannanase is higher in the thermoinhibition tolerant genotype.